Структурно-динамічні властивості апікальної мембрани ентероцитів кишечнику телят за ентеропатології та комплексної терапії із застосуванням фосфоліпідовмісної БАД - Мельничук, Д.О.; Грищенко, В.А.; Хижняк, С.В.; Кисіль, О.О.; Войціцький, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
We have found changes in the physical, structural, and dynamic properties of the apical membrane of intestine enterocytes of 1-month-old calves' which had been ill with neonatal dyspepsia. An effective impact of complex therapy using a biologically active additive with reparative function on the base of milk phospholipids for the correction of the available data is shown.